(untitled) (Itinera, 2021)
Following the tradition of the philosophical dialogue, we reimagine our real conversation where we come to understand our respective views on the sublime. We aim to do so in a way that respects both the sublime’s complex philosophical past and its emerging future in empirical research. As in a traditional dialogue, this contrivance is supposed to enact a philosophical exchange. The following conversation reveals the interlocutors’ diverging, converging, and shifting understanding of the sublime in a way that a verbatim interview transcript or a co-authored treatise could not. Moreover, its setting is indicative of the conversation’s current moment: the scene is the virtual Zoom room.